A Case Study of Social Enterprise: Enhancing Sustainable Growth through Agency X in Malaysia - Ahmad Puad, Farhawahidah (JBS Nexus, 2026)
This study analyses how Agency X balances social mission and operational sustainability as a community-based social enterprise in Malaysia. Using a qualitative case study approach, the research examines how the organisation operationalises its social mission, sustains organisational activities, and manages tensions between social objectives and operational viability. Data were collected through two site visits, organisational observations, informal semi-structured discussions with management representatives and operational workers, and documentary analysis involving organisational materials, business model documents, programme records, and operational reports. Thematic analysis was applied to identify recurring organisational patterns aligned with the research objectives. The findings demonstrate that Agency X operationalises its social mission through community-centred employment, food assistance activities, training programmes, and collaborative operational practices. Organisational sustainability is supported through hybrid revenue streams, institutional partnerships, and adaptive operational arrangements. However, tensions emerged between inclusion and efficiency, mission orientation and commercial sustainability, as well as growth ambitions and operational capacity. The findings support existing social enterprise literature suggesting that hybrid organisations continuously negotiate competing organisational priorities rather than fully resolving them. The study contributes to social enterprise literature by providing empirical insights into how Malaysian community-based social enterprises sustain operational continuity while maintaining social legitimacy. The case further highlights that long-term sustainability requires strategic focus, disciplined operational management, and selective organisational growth rather than uncontrolled expansion.